THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CASH HOLDING ON INCOME SMOOTHING IN INDONESIAN MANUFACTURING COMPANIES - Desmiwerita Desmiwerita; Yuli Ardiany; Melli Herfina; Dorris Yadewani; Miftahul Jannah (AIBPM Publisher, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) on income smoothing and to analyze the moderating role of cash holding in the relationship between GCG and income smoothing practices among manufacturing companies listed on the Indonesia Stock Exchange during the 2012–2023 period. The study employs a quantitative approach using panel data regression and Moderated Regression Analysis (MRA). The sample consists of 390 firm-year observations selected through purposive sampling. The variables analyzed include income smoothing as the dependent variable, Good Corporate Governance as the independent variable, cash holding as the moderating variable, and profitability (ROA) and leverage (DER) as control variables. The results indicate that Good Corporate Governance negatively and significantly affects income smoothing, suggesting that stronger governance mechanisms improve monitoring effectiveness and reduce managerial opportunism in financial reporting. Cash holding positively and significantly affects income smoothing, indicating that firms with higher liquidity levels tend to engage more in earnings smoothing practices. Furthermore, cash holding significantly moderates the relationship between Good Corporate Governance and income smoothing, implying that liquidity conditions influence the effectiveness of governance mechanisms in constraining managerial opportunism. This study contributes to agency theory by demonstrating that governance effectiveness in reducing income smoothing depends not only on governance quality but also on firms’ liquidity conditions. The findings provide practical implications for investors, regulators, and corporate management regarding the importance of governance quality and liquidity management in maintaining financial reporting credibility.